Theobromine prevents affective symptoms of nicotine withdrawal by modulating the neuroendocrine and immune systems, as well as the glutathione mechanism in the hippocampus - Qi Zhang; Yu Tian; Baojiang He; Wenjuan Zhang; Xingyu Liu; Jufang Hao (IBRO Neuroscience Reports)
Currently, nicotine withdrawal symptoms pose a significant challenge in tobacco cessation efforts, particularly withdrawal affective symptoms, such as anxiety and depression like behavior. However, the underlying mechanisms of these symptoms remain poorly understood. Emerging evidence implicates the hippocampus, a key region in the limbic system, involved in emotional regulation. In this study, we employed transcriptome sequencing, untargeted metabolomics, and integrative multi-omics analysis to elucidate the molecular mechanisms underlying nicotine withdrawal-induced affective symptoms in the hippocampus of male C57BL/6J mice. Our findings corroborate previous research linking nicotine withdrawal symptoms to dysregulation of neuroendocrine pathways and inflammatory processes within the brain. Importantly, we identify impaired glutathione metabolism as a significant contributing factor to the development of these symptoms. Furthermore, our investigation reveals that theobromine, a principal psychoactive compound found in cocoa, exerts a potent therapeutic effect in alleviating nicotine withdrawal affective symptoms through diverse mechanisms. In addition to its modulation of neuroendocrine pathways and inflammation, theobromine's ability to restore glutathione metabolism in the hippocampus emerges as a pivotal aspect of its pharmacological action.